Pro JavaFX™ Platform: Script, Desktop and Mobile RIA with Java™ Technology - Weaver, James L. (Apress, 2012)
This book is written in a tutorial-style, with lots of hands-on examples and instructions that walk you through using and understanding them. Chapter 1, “Getting a Jump Start in JavaFX,” helps you learn how to develop applications in the JavaFX language, brings you up-to-date on the brief history of JavaFX, and shows you how to get the JavaFX software development kit. It then walks you through the process of compiling and running JavaFX applications, and teaches you a lot about the JavaFX language and API while walking through example application code.0